L’incontinence de la chair - Julien Théry (Cahiers d’histoire.)
The norms of Christian life and clerical authority were imposed in depth in Western societies from the thirteenth century onward, a time of a pastoral revolution, whose development was conditioned by the establishment of unprecedented papal control over members of the high ecclesiastical hierarchy. The exercise of this control notably took the singular form of frequent investigative procedures against prelates who were accused of various « excesses » or « enormities », among which breaches of chastity, grouped under the name « incontinence of the flesh », were very frequently associated with faults in spiritual and temporal government. This paper examins the particular meaning of these accusations of lustful behavior in such a context.